2015
DOI: 10.3109/10717544.2015.1074765
|View full text |Cite
|
Sign up to set email alerts
|

Advances in nanotechnology-based carrier systems for targeted delivery of bioactive drug molecules with special emphasis on immunotherapy in drug resistant tuberculosis – a critical review

Abstract: From the early sixteenth and seventeenth centuries to the present day of life, tuberculosis (TB) still is a global health threat with some new emergence of resistance. This type of emergence poses a vital challenge to control TB cases across the world. Mortality and morbidity rates are high due to this new face of TB. The newer nanotechnology-based drug-delivery approaches involving micro-metric and nano-metric carriers are much needed at this stage. These delivery systems would provide more advantages over co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 204 publications
(180 reference statements)
0
32
0
4
Order By: Relevance
“…Similar to liposomes, the bilayer structure of niosomes allows them to carry both hydrophilic and hydrophobic moieties; however, the materials used to make them are usually cheaper and more accessible, while enabling similar circulation times in vivo. Further, some evidence has shown that they can be less permeable to oxygen than liposomes, which could be advantageous in certain applications . Finally, early work has shown that niosomes may possess adjuvant‐like properties by enhancing the production of antibodies against BSA compared to FCA…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
“…Similar to liposomes, the bilayer structure of niosomes allows them to carry both hydrophilic and hydrophobic moieties; however, the materials used to make them are usually cheaper and more accessible, while enabling similar circulation times in vivo. Further, some evidence has shown that they can be less permeable to oxygen than liposomes, which could be advantageous in certain applications . Finally, early work has shown that niosomes may possess adjuvant‐like properties by enhancing the production of antibodies against BSA compared to FCA…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
“…In the same drug concentrations, the amount of drug delivered to brain from SLNs reported to be higher than that from neutral and cationic formulations (Lockman et al, 2004). These carriers also possess hallmarks such as biocompatibility, ease of production and regulatory approval, which have been found to be a boon for the biomedical applications (Raza et al, 2013a;Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, efficient therapy is achieved with reduced side effects and toxicity [45]. For PDD of ATDs various nanocarrier systems as Vesicle-based, lipid based, emulsion based, and polymer based are formulated and tested [46]. Until now, no nanoformulation of ATDs intended for PDD has been in the market.…”
Section: Need Of Pdd Of Nps Containing Atdsmentioning
confidence: 99%